Road to Rio - Norman Z McLeod; Hope, Bob, 1903-2003; Dorothy Lamour; Frank Faylen; Gale Sondergaard; George Meeker; Joseph Vitale; Bing Crosby (USA Bing Crosby Productions, 1947)
Another in the excellent Hope and Crosby 'Road To' series. Scat Sweeney, and Hot Lips Barton, two out of work musicians, stow away on board a Rio bound ship, after accidentally setting fire to the big top of a circus. They then get mixed up with a potential suicide Lucia, who first thanks them, then unexpectedly turns them over to the ship's captain. When they find out that she has been hypnotised, to go through a marriage of convenience, when the ship reaches Rio, the boys turn up at the ceremony, in order to stop the wedding, and to help catch the crooks.
Another in the excellent Hope and Crosby 'Road To' series. Scat Sweeney, and Hot Lips Barton, two out of work musicians...
Edmund Beloin
Language(s): English Subtitle(s): No Subtitle
Keywords: Comedy; Musical; Romance; Adventure